Impact of innovation on corruption - Ismaily Johari; Saifuzzaman Ibrahim; Nik Ahmad Sufian Burhan (Penerbit Universiti Kebangsaan Malaysia, 2018)
Corruption causes inefficiencies in the economic, social and political development. This study investigates the relationship between the level of innovation and the level of corruption in 131 countries. We employ a cross-sectional analysis and find that innovation is positively significant in reducing corruption. Our finding suggests that innovation causes the industries and private sectors to become less dependent on the favoritism from the public officials and authorities. They are more encouraged to innovate to gain the competitive advantage and make real profits. We believe that innovation increases the relative return on production and causes a decrease in corruption activities. Therefore, the government and other relevant bodies should set up a policy to increase the level of innovation, as part of their strategy to indirectly combat the problem of corruption.